P1317 Very late onset of platypnoea orthodeoxia syndrome as first clinical scenario of patent foramen ovale. (17th January 2020) - Binno, S M; Moderato, L; Pastorini, G; Matrone, B; Aschieri, D; Moccia, L; Magri, P; Franco, C; Villani, G Q
Abstract: : We report a case of a 83-year-old female, who had an admission for dyspnea. Laboratory showed D-dimer 1000 ng/ml, haemoglobin 12.4 mg/dL, CPR 0.08mg/dl whereas on Arterial Blood Gas test she had hypoxia with respiratory alkalosis. In view of suspected pulmonary embolism, she underwent Thoracic Computed Tomography scan that excluded it. During the stay the patient seemed more symptomatic while in standing position(with SpO2s 89% while supine plunging to 50% while standing): ABGs were performed both standing (reservoir 15 l/min pH 7.50, pO2 37.2 mmHg, pCO2 37.1 mmHg, HCO3 28.9 mmol/l) and recumbent position (reservoir 15 l/min pH 7.47, pO2 65.5 mmHg, pCO2 35.1 mmHg, HCO3 25.6 mmol), showing a difference of 28 mmHg. Subsequently the patient underwent v/p pulmonary scintigraphy: no signs of pulmonary embolism though it revealed a multiple focus of capitation Tc-99m macro aggregated albumin in brain, thyroid and kidneys (IMG top), compatible for veno-arterial shunt. Trans-esophageal echocardiography (TOE) revealed a massive stretched patent foramen ovale (PFO) with continuous right-to-left shunting through the atria. The bubble test (IMG bottom) confirmed the presence of patency along with sudden passage of microbubbles through the foramen. Qp/Qs = 0.8, due to volume overload in the left atrium from the right atrium. The imaging along with clinical scenario confirmed the suspected diagnosis of platypnea-orthodeoxia, finding the patent foramen ovale as the anatomical cause. Platypnea-orthodeoxia syndrome is a clinical condition characterized by dyspnea. Typically blood oxygen saturation declines with standing position while it resolves with recumbent. The classification entails 3 groups: intracardiac shunting (most common presentation), pulmonary shunting, ventilation-perfusion mismatch. Presence of multiple focus of albumin macroaggregates outside the lungs in v/p scintigraphy examination is suggestive for veno-arteriuous shunt: without shunt, normally all the albumin aggregates are hampered in the lungs' field. Images in bottom are taken in sequence from a single acquisition during the TOE, in one single cardiac beat. Here is depicted the evidence of the PFO, the influx of bubbles in the right atrium and the instantaneous and massive shunt of the bubbles across the interatrial septum, in the left atrium. Usually the diagnosis is performed within 55 years old: it is interesting how late the diagnosis occurred in this patient with such resounding clinical manifestation. Top: Scintigraphy with ventilation and perfusion lung scan sequences. Next, scintigraphy with capitation of Tc-99m macro aggregated albumin in brain, thyroid and kidneys. Bottom, Transesophageal echocardiogram: images taken within the same heart beat proving right-to-left passage of bubble across the septum.